U-Pb age and Hf-O isotopes of detrital zircons from Hainan Island: Implications for Mesozoic subduction models - Jiang, X.; Li, X.; Collins, William; Huang, H. (Elsevier BV, 2015)
A compilation of magmatic ages from the Mesozoic South China Block suggests a number of "magmatic quiescence" periods at ca. 205-195 Ma, ca. 150-140 Ma and ca. 125-115 Ma, casting doubt on tectonic models that suggest ongoing Andean-type subduction along the South China continental margin. However, SIMS U-Pb analyses on two detrital zircon samples from the Cretaceous Lumuwan Formation on Hainan Island, southeast China, reveal three major age peaks at ca. 120 Ma, ca. 155 Ma and ca. 235 Ma. Zircons of these ages are mostly euhedral and show typical magmatic oscillatory zoning, suggesting short-distance transport from nearby magmatic sources. The extremely rare occurrence of ca. 120 Ma magmatic records onshore suggests that detrital zircons of this age population may be derived from a source proximal to Hainan Island but presently missing. Therefore, our data provide new evidence for ongoing magmatic activity in late Mesozoic South China. In situ Hf and O isotope analyses of the Mesozoic detrital zircons reveal large variations in both eHf(t) (-21.2 to 10.5) and d18O (4.4‰ to 13.6‰) values. A general negative correlation between them suggests the reworking of old supracrustal materials (average crustal residence age of ca. 2.0Ga) by juvenile mantle-derived magmas. The progression of increasing eHf(t) and decreasing d18O values of zircons from the Triassic to the Cretaceous suggests progressive crustal growth during the Mesozoic. The results are consistent with hybridization at an active continental margin. We briefly review tectonic models for the Indosinian orogeny and suggest that the petrologic evidence indicates that Mesozoic magmatism was part of the circum-Pacific accretionary orogens that formed along the continental margin of East Asia no later than ca. 250Ma and continued at least to the late Cretaceous.